Matching‐adjusted indirect comparison of isatuximab plus carfilzomib and dexamethasone with daratumumab plus lenalidomide and dexamethasone in relapsed multiple myeloma. (1st February 2023) - Richter, Joshua; Lin, Peggy L.; Garcia‐Horton, Viviana; Guyot, Patricia; Singh, Erin; Zhou, Zheng‐Yi; Sievert, Mark; Taiji, Riley
Abstract: Backgound: Lenalidomide‐based regimens are commonly used for early relapse in patients with relapsed and/or refractory multiple myeloma (RRMM) receiving at least one prior line of therapy. In the absence of head‐to‐head comparison, matching‐adjusted indirect comparison (MAIC) was conducted to demonstrate efficacy and safety of isatuximab+carfilzomib+dexamethasone (Isa‐Kd) versus daratumumab + lenalidomide + dexamethasone (Dara‐Rd) in RRMM. Methods: Patient‐level data from IKEMA trial (Isa‐Kd, n = 179) were matched to aggregate data from POLLUX (Dara‐Rd, n = 286). Hazard ratios (HR) and 95% confidence intervals (CI) for progression‐free survival (PFS) and overall survival (OS) were generated by weighted Cox proportional hazard models. Odds ratios (OR), 95% CI, and p ‐value were calculated for ≥very good partial response (≥VGPR) and treatment‐emergent adverse events (TEAEs). Results: After matching, no significant differences were observed between Isa‐Kd and Dara‐Rd in baseline characteristics except for patients with >3 prior lines (0.0% vs. 4.9%). Isa‐Kd showed significantly better PFS (HR [95% CI]: 0.46 [0.24–0.86]; p = 0.0155), statistically non‐significant improvement favoring Isa‐Kd in OS (0.47 [0.20–1.09]; 0.0798), and ≥VGPR (OR [95% CI]: 1.53 [0.89–2.64]; p = 0.1252) than Dara‐Rd. Odds of occurrence were significantly lower for some all‐grade and grade 3/4 TEAEs with Isa‐Kd than Dara‐Rd. Conclusion: These results support Isa‐Kd as an efficacious treatment for early relapse in non‐lenalidomide refractory patients. Abstract : Matching‐adjusted indirect comparison results for Isa‐Kd vs. Dara‐Rd: Kaplan‐Meier curves of progression‐free survival before matching and after inclusion criteria selection (A) and after matching (B); Kaplan‐Meier curves of overall survival before matching and after inclusion criteria selection (C) and after matching (D). CI, confidence interval; Dara‐Rd, daratumumab + lenalidomide + dexamethasone; HR, hazard ratio; Isa‐Kd, isatuximab + carfilzomib + dexamethasone. *Statistically significant at 0.05 level.